Health Promotion in Bulgarian Balneotherapy Centers - Diana Popova-Dobreva (Editura Universitatii Transilvania din Brasov, 2023)
Following Johnston, Puczko, Smith, and Ellis (2011), Hitz et al. (2014) define wellness tourism as: 'involving people traveling to a different place to proactively pursue activities that maintain or enhance their personal health and well-being, and who are seeking unique, authentic or location-based experiences or therapies that are not available at home'. The present study reveals the possibilities for health promotion by analyzing the services offered in 51 certified balneotherapy centers in Bulgaria.